POSSIBILITIES OF TEACHING VIRTUALIZATION TECHNOLOGIES AND ITS AUTOMATION USING VMWARE VSPHERE TECHNOLOGY - Milan, KLEMENT (Trends in education, 2022)
The use of virtualization and virtualization technologies in educational institutions seems to be very beneficial and from the point of view of teachers and students as stimulating. It is possible to use them not only to ensure the operation of school information systems, but also for the teaching of pupils or students. For student experiments, but usually there are no means to build the necessary technological background, and this partly applies to the possibility of deployment in a production environment. The range of virtualization technologies is currently very extensive and can cover the full range of user needs, from desktop operating system virtualization, through server virtualization to virtualization and consolidation of individual services. The presented article deals with current issues of construction, operation and preparation of consolidated data centers for teaching advanced management and operation of virtualization technologies based on VMware vSphere. It introduces the reader not only to the concept of virtualization, but also the necessary hardware and software infrastructure needed for its implementation, including the possibility of automating the preparation of learning environments using PowerCLI and PowerShell.
Keywords: Virtualization technology; virtualization; virtualization datacenter; VMware; vSphere; vCenter.